SYSTEMATIC LITERATURE REVIEW: THE EFFECT OF PROBLEM-BASED LEARNING MODELS ON STUDENTS' MATHEMATICAL PROBLEM-SOLVING SKILLS AND EMOTIONAL INTELLIGENCE - Saraswati, Emiliana; Hakim, Lukman El; Aziz, Tian Abdul (Universitas Sembilanbelas November Kolaka, 2025)
In modern education, two elements are considered crucial: mathematical problem-solving ability and students' emotional intelligence. Both are seen as vital assets for facing the challenges of the 21st century. The Problem Based Learning (PBL) model is often hypothesized as an approach that can sharpen both of these domains simultaneously. However, this hypothesis needs to be proven by synthesizing existing empirical findings. Therefore, this systematic literature review was conducted to answer the question: to what extent does PBL influence these two abilities? Guided by the Systematic Literature Review (SLR) method and the PRISMA framework, we searched and screened various research articles from scientific databases. We focused on experimental and quasi-experimental studies published in the last decade. After a rigorous selection process, a number of eligible articles were identified and analyzed. Our analysis reveals a consistent finding: the implementation of the PBL model has a proven, positive, and significant impact on students' mathematical problem-solving abilities. In a PBL environment, students do not just memorize formulas; they are actively involved in understanding problems, designing solution strategies, and evaluating outcomes. Furthermore, the collaborative and interactive learning process in PBL also turns out to be fertile ground for nurturing emotional intelligence. Students learn to manage their emotions when facing difficulties, build intrinsic motivation, empathize with teammates, and hone their social skills. From this synthesis, we can conclude that the Problem-Based Learning model is more than just a strategy to improve math scores. It is a holistic approach that successfully bridges the development of critical thinking skills with emotional maturity. This finding underscores the urgency of further integrating PBL into the curriculum, aiming to shape a generation that is not only intelligent but also resilient and collaborative.